Ecotoxicity of pyridinium based ionic liquids: A review - Mohamed, N.F. (Trans Tech Publications Ltd, 2014)
Ionic Liquids (ILs) are an exciting class of compounds with unique properties that make them attractive for industrial applications. Pyridinium-based ILs have been used in many applications, such as organic synthesis, electrochemical applications, biocatalysis, and polymerization. Although intensive information and data regarding to the physical and thermodynamic properties of ILs have been reported and continuously published, only limited data with regards to the toxicity and ecotoxicity of ILs were reported. Toxicity tests are conducted against many aquatic organisms such as: Guppy fish, Gold fish, and Zebra fish, besides many different strains of Microorganisms such as: Staphylococcus aureus, E. coli, and Salmonella typhi, and yet more research regarding the toxicity of ionic liquids is yet to be conducted to increase the toxicity profile for these valuable chemicals. Â© 2014 Trans Tech Publications, Switzerland.